Biomarkers of gut injury in neonates – where are we in predicting necrotising enterocolitis? - Howarth, Claire; Banerjee, Jayanta; Eaton, Simon; Aladangady, Narendra (Frontiers in Pediatrics, 2022)
Despite advances in neonatal care Necrotising Enterocolitis (NEC) continues to have a significant mortality and morbidity rate, and with increasing survival of those more immature infants the population at risk of NEC is increasing. Ischaemia, reperfusion, and inflammation underpin diseases affecting intestinal blood flow causing gut injury including Necrotising Enterocolitis. There is increasing interest in tissue biomarkers of gut injury in neonates, particularly those representing changes in intestinal wall barrier and permeability, to determine whether these could be useful biomarkers of gut injury. This article reviews current and newly proposed markers of gut injury, the available literature evidence and considers how effective they are in clinical practice.